Analisis Harga Saham Pada Perusahaan Siklis dan Non-Siklis Akibat Konflik Israel-Palestina (Studi Empiris) - Okta Bahari, Defi; Mutasowifin, Ali (IPB University, 2025)
The conflict between Palestine and Israel has a long and complex history that has persisted for over half a century without resolution. This conflict escalated again with an attack by Israel on October 7, 2023, causing significant casualties and damage in Gaza. This study aims to analyze the impact of the Israel-Palestine conflict on the stock prices of cyclical and non-cyclical companies. The variables in this study are the stock prices of cyclical companies (McDonald's and Starbucks) and non-cyclical companies (Unilever and Nestlé). The research was conducted on companies listed on the S&P Dow Jones. The data analysis methods used include descriptive tests, normality tests, homogeneity tests, Friedman tests, and Kruskal-Wallis tests using SPSS version 23. The results of the study indicate significant changes in the stock prices of cyclical and non-cyclical companies during the conflict. McDonald's and Starbucks experienced significant stock price declines, while Unilever and Nestlé showed greater stability. This research provides insights for investors and financial analysts in managing portfolios during periods of geopolitical uncertainty.